Environmental policy in a two sector endogenous growth model - Frank Hettich; Minna Selene Svane (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1998)
This paper analyses policy measures within a two sector endogenously growing economy with pollution. Pollution is either generated by production or by the use of physical capital in production, and can be reduced by public abatement activities. In this generalized Uzawa-Lucas model, the effects of fiscal policy are derived for all core variables and ratios. In addition, the optimal taxation rules are derived. If a pollution tax is not available it turns out that a first best solution may be reached by use of factor income taxation. Additionally, the effects and the possibility of environmental policy are complemented for a small open economy.
Keywords: D62; O41; Q28; F43; 330; endogenous growth; environmental externality; optimal taxation; international capital mobility